SPHENOBAIERA IKORFATENSIS (SEWARD) FLORIN FROM THE LOWER CRETACEOUS OF HUOLINHE, EASTERN INNER MONGOLIA, CHINA - Ge S.; Lydon S.J.; Watson J. (My University, 2003)
Sphenobaiera ikorfatensis (Seward) Florin from the Lower Cretaceous Huolinhe Formation in the Huolinhe coal-mining area, eastern Inner Mongolia, China, is identified, described and figured. Comparison with the type material of Sphenobaiera ikorfatensis (Seward) Florin from West Greenland confirms its identity. About 20 Chinese leaf specimens are known with well preserved cuticle which is closely similar to the Greenland leaves but more papillate. The palaeoclimatic and phytogeographic significance of the occurrence of this species is discussed in relation to the suggestion that West Greenland, north-east China and eastern Siberia were in the same phytogeographic region during the Lower Cretaceous.
Keywords: SPHENOBAIERA; GINKGOALES; LOWER CRETACEOUS; MONGOLIA; CHINA; PALAEOGEOGRAPHY; Mesozoic::Cretaceous; Мезозой::Меловая